Gastrointestinal symptoms in children with acute neuroinfections - A.I. Markov; S.O. Kramarov (Zaslavsky O.Yu., 2018)
Background. In cases of severe forms of infectious diseases, in addition to local inflammation, secondary lesions of the gastrointestinal organs may occur. We aimed to study the semiotics and epidemiology of gastrointestinal symptoms in children with acute neuroinfection. Materials and methods. This observational, retrospective, case-control study. We analyzed cases of in-patient treatment of children aged 1 month to 18 years with acute neuroinfections (meningitis, encephalitis and encephalomyelopolyneuropathy). Results. The study included 117 patients with acute central nervous system infections. Clinical symptoms of gastrointestinal infection were observed in 83 (70.9 %) children. Among revealed symptoms, disorders of intestinal motility, such as constipation and diarrhea, were prevalent. Manifestations of hepatobiliary system dysfunction included increased transaminase level (alanine aminotransferase (ALT), alkaline phosphatase, gamma-glutamyltransferase (GGTF)) and/or ultrasound changes (enlargement, diffuse structural changes) and were observed in 39.1 % of patients. Among the laboratory parameters, elevated ALT level was observed in 8.3 % of patients, bilirubin was elevated in only one child, alkaline phosphatase was above the age norm in 11.8 %, an increased GGTF above the age norm was observed in 31.3 % of patients. The level of intestinal fatty acid binding protein (I-FABP) was elevated in 86.4 %, and L-type fatty acid binding protein (L-FABP) - in all (100 %) children. Clinical manifestations of gastrointestinal dysfunction (the presence of at least one of the gastrointestinal symptoms) had an inverse relationship with the child's age (rpb = -0.19, p = 0.033), correlated with staying in intensive care unit (odds ratio (OR) = +5.25; 95% confidence interval (CI) 1.62-16.97), artificial ventilation (OR = +4.5; 95% CI 1.00-21.69) and level of I-FABP (rpb = 0.34, p = 0.019). Conclusions. Among gastrointestinal symptoms in children with acute neuroinfections, disorders of intestinal motility, such as constipation and diarrhea, are the most common ones. Hepatobiliary system dysfunction is mainly manifested by moderate changes in laboratory parameters. I-FABP and L-FABP biomarkers are highly sensitive tests for the diagnosis of damage to the gastrointestinal tract and hepatobiliary system.